Low density mammography is associated with increased carotid intima-media thickness in middle aged premenopausal women - Hamidreza Talari; Amin Payandeh; Sara Masoudi; Peyman Family; Gholam-Abbas Moussavi; Nushin Moussavi (International Archives of Health Sciences, 2023)
Objectives: As the hormonal status of women does influence both mammographic breast density and atherosclerosis, the aim of the study was to evaluate the association between breast density on mammography and carotid intima-media thickness (CIMT).Methods: Two-hundred premenopausal women with mammographic breast density of one (n=100) or four (n=100) were selected for this cross-sectional study. CIMT was measured according to the guidelines of Mannheim Consensus. The correlation between mammographic breast density and CIMT was assessed.Results: Mean age was 45.9±3.4 years and 45.8±3.2 years in the groups with mammographic density of 1 and 4, respectively, which showed no significant difference. CIMT correlated with age with a Pearson Correlation Coefficient of 0.470 (p<0.001). CIMT was significantly higher in women with ACR-mammographic density of 1 (p<0.001).Conclusion: Women with mammographic breast density of 1 revealed a higher CIMT. Further studies evaluating breast density and CIMT in pre- and postmenopausal women and assessing simultaneously the serum hormone level could give more information about the cause and effect of this correlation.